Facile strategy for advanced selectivity and sensitivity of SnO2 nanowire-based gas sensor using chemical affinity and femtosecond laser irradiation - Park, Hyoungwon; Kim, Jae Hun; Shin, Won Sang; Mirzaei, Ali; Kim, Yoon Jun; Kim, Sang Sub; Halik, Marcus; Park, Changkyoo (Sensors and Actuators B-Chemical, 2022)
This study proposes an effective strategy to improve the selectivity and response of SnO2 nanowire (NW)-based gas sensors. Self-assembled monolayer (SAM) functionalization of SnO2 NWs enhances the gas selectivity by tuning the surface chemical states. Different chemical moieties with alkyl and fluoroalkyl of the SAM molecules are adopted for the chemical affinities toward the corresponding target gas molecules. The alkyl and fluoroalkyl moieties show excellent selectivity toward CH4 and C3F8, respectively, owing to the strong chemical affinity between the moieties and gases. Post-treatment femtosecond (FS) laser irradiation with different laser fluences is applied to the SAM-functionalized SnO2 NW-based gas sensor. The FS laser-irradiated SnO2 NWs show an enhanced sensor response with higher resistance values and shorter response and recovery times compared to those of the pristine SnO2 NWs. Transmission electron microscopy analysis reveals that the FS laser irradiation induces the formation of embossing surface on the SnO2 NW, creating additional gas adsorption sites. Moreover, twin structures develop on the SnO2 NWs with increasing laser fluences. Electron energy loss spectroscopy analysis supports that the FS laser irradiation creates non-stoichiometric SnO and SnOx phases, providing O vacancies and improved response.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Femtosecond laser irradiation; Gas sensors; Self-assembled monolayers; SnO; Surface functionalization